Analisis Kesuksesan E-Billing pada Kantor Pelayanan Pajak Pratama Palembang Ilir Timur Menggunakan Structural Equation Modeling - Lestari, Rizky Nurfitri; Santi, Rusmala; Jaya, Irfan Dwi (Department of Informatics Engineering, 2021)
This study discusses the application of Structural Equation Modeling (SEM) and measures the success of e-billing implementation at the Palembang Ilir Timur Pratama Tax Office and the factors that influence its success. E-billing is developed and managed by the Directorate General of Treasury. There are 100 thousand e-billing users registered at the Palembang Ilir Timur Pratama Tax Office. Based on the analysis results obtained standardized residual covariances matrix values no smaller than -2.58 or greater than 2.58 and the probability of showing a value of 0.080 which means that the value meets the interpretation requirements that the model can be accepted. The results of this study indicate that the success rate of e-billing implementation is at the level of 78% (